Assistance in Skills Training for Making Herbal Mouthwash Green Tea Leaves and Its Herbal Combinations for Posbindu Partner Cadre - Dicki Bakhtiar Purkon; Mimin Kusmiyati; Elvi Trinovani; Faizah Min Fadhlillah; Yayat Sudaryat; Zahra Anggraeni; Tanika Miatul Hadid; Afifah Rahmawati (Media Karya Kesehatan, 2022)
The level of knowledge and awareness of the Indonesian people towards preventive efforts of various diseases related to the oral cavity and teeth has not been optimal. The importance of the role of self-effort in optimizing oral cavity hygiene and inhibiting the growth of various types of harmful bacteria that can lead to plaque formation, dental caries, causes of gingivitis, and periodontitis, such as: bacterial species Streptococcus mutans and Porphyromonas gingivalis. The combination of green tea, cloves, cinnamon bark, and mint leaves containing secondary metabolites from the sterols, tannins, phenols, saponins, and flavonoids groups has traditionally been used as antibacterial, anti-plaque and anti-aviation. The purpose of this community service activity is to improve understanding of health and prevention of infections in the oral cavity and teeth, as well as assistance in training skills in making herbal combination mouthwash with simple formulations for Posbindu partners. This activity was attended by lecturers and students of the D-3 Pharmacy Study Program, Department of Pharmacy, Poltekkes Kemenkes Bandung. Changes in health knowledge and skills of Posbindu partners were evaluated by giving pre-test and post-test questions. In the results of the evaluation of health understanding and skills, there was an increase in the total score of Posbindu partners in the 1st session of 20.41% from 67.35% to 87.76% (14 people were achieved, initially only 7 people exceeded the minimum score limit of 60.00%; N=14). Meanwhile, in the second session of Posbindu partners, the score increased by 28.57% from 63.64% (pre-test) to 92.21% (post-test) with the number of people who exceeded the minimum score limit of 11 people (post-test) from the pre-test results. the previous test was only 5 people (N=11). Thus, the better the health knowledge, attitudes, and skills of Posbindu partners in processing various herbal ingredients into herbal mouthwash products, it will create an increase in the degree of oral and dental health for the community. Keywords:  Cloves, green tea leaves, mint leaves, cinnamon bark, herbal mouthwash.